Effects of mine tailing exposure on early life stages of cod (Gadus morhua) and haddock (Melanogrammus aeglefinus) - Farkas, Julia; Nordtug, Trond; Svendheim, Linn Hjelmeland; D Amico, Elettra; Davies, Emlyn John; Ciesielski, Tomasz Maciej; Jensen, Bjørn Munro; Kristensen, Torstein; Olsvik, Pål Asgeir; Hansen, Bjørn Henrik (Environmental Research, 2021)
Mining and processing of minerals produce large quantities of tailings as waste. Some countries, including Norway, allow disposal of mine tailings in the sea. In this study we investigated the impacts of tailings from a calcium carbonate (CaCO3) processing plant on early live stages of haddock ( Melanogrammus aeglefinus ) and Atlantic cod ( Gadus morhua ). Fish eggs (3 days post fertilisation; dpf) were exposed for 48 h to three concentrations of tailings, nominally 1 mg L −1 (low, L); 10 mg L −1 (medium, M) and 100 mg L −1 (high, H); with L and M representing concentrations occurring at tailing release points. Results show that tailings rapidly adhered to eggs of both species, causing negative buoyancy (sinking of eggs) in M and H exposures. While tailings remained on egg surfaces in both species also after exposure termination, adhesion seemed more pronounced in cod, leading to larger impacts on buoyancy even after exposure. Tailing exposure further induced early hatching and significantly reduced survival in M and H exposed embryos in both fish species, and in cod from the L exposure group. Moreover, tailing exposure caused reduced survival and malformations in larvae, potentially related to premature hatching. This study shows that mineral particles adhere to haddock and cod eggs, affecting egg buoyancy, survival and development.